Analisis Ekonomi Publik Menurut Perspektif Islam - Billi Jenawi; Devani Tarigan; Ahmad Wahyudi Zein (Journal of Islamic Economics and Finance, 2025)
In many developing countries today, the capitalist economic system still dominates. Not infrequently, this system causes various problems when applied in the governance of a country's economy. These problems generally arise because policies, regulations, and public financial management have not been directed at the principles of Islamic economics (sharia). In fact, the public economic system based on sharia provides guarantees for the fulfillment of state needs (income) and people's needs (expenditure). In addition, the rampant practice of misappropriation such as fraud and corruption has also caused the loss of public trust in public economic management. This condition contributes to the economic crisis and exacerbates the suffering of the people. Therefore, to solve these problems, the government needs to adopt a public economic concept based on Islamic values, because this system has been proven to be able to encourage justice and improve social welfare. This study uses a qualitative method with a literature study approach. The findings in the study indicate that there are various sources of income in the Islamic economy that can be utilized as public finances, such as Ghanimah, Fa'i, Jizyah, Kharaj, Waqf, Nawaib, Zakat, Infak, Sedekah, and 'Usr. Meanwhile, state expenditure is allocated to fulfill basic community needs, state defense and administration, education, social security, and development of infrastructure and public facilities. Keywords: Capitalism, Economic system, Public sector In many developing countries today, the capitalist economic system still dominates. Not infrequently, this system causes various problems when applied in the governance of a country's economy. These problems generally arise because policies, regulations, and public financial management have not been directed at the principles of Islamic economics (sharia). In fact, the public economic system based on sharia provides guarantees for the fulfillment of state needs (income) and people's needs (expenditure). In addition, the rampant practice of misappropriation such as fraud and corruption has also caused the loss of public trust in public economic management. This condition contributes to the economic crisis and exacerbates the suffering of the people. Therefore, to solve these problems, the government needs to adopt a public economic concept based on Islamic values, because this system has been proven to be able to encourage justice and improve social welfare. This study uses a qualitative method with a literature study approach. The findings in the study indicate that there are various sources of income in the Islamic economy that can be utilized as public finances, such as Ghanimah, Fa'i, Jizyah, Kharaj, Waqf, Nawaib, Zakat, Infak, Sedekah, and 'Usr. Meanwhile, state expenditure is allocated to fulfill basic community needs, state defense and administration, education, social security, and development of infrastructure and public facilities.